Aspectos eletrônicos e estruturais do grafeno e derivados: um estudo teórico-experimental - Marcos Henrique Diniz Guimaraes (2010)
In this work we study the electronic and structural properties of graphene and graphene based materials by means of experimental and theoretical techniques. By means of ab-initio calculations using the Density Funcional Theory (DFT), we study the effect of pressure on graphene multi-layers. We look for an explanation for experimental results on the charge injection in these materials. Theoretical models for few-layer graphene under pressure in vacuum and in a water environment are studied. We study experimentaly the electronic properties of graphene samples made by the mechanical exfoliation technique on a Si/SiO2 substrate, using electronic transport and scanning probe microscopy techniques combined with electronic transport measurements. The electronic and magnetic properties of hydrogenated or oxidated graphene based materials are studied by DFT calculations. We study the properties, like edge states, for graphene nanoribbons embebedded in graphane and graphene oxide structures. The difference in energy between the ferromagnetic and anti-ferromagnetic states of the ribbon are calculatedas a function of the its width. We also use Group Theory to describe the electronic and vibrational properties of graphene multi-layers and derive the selection rules for optical absorption and electron-phonon scattering.